2021
DOI: 10.1590/1980-5373-mr-2021-0050
|View full text |Cite
|
Sign up to set email alerts
|

SnO2/ZnO Heterostructure as an Electron Transport Layer for Perovskite Solar Cells

Abstract: This work reports a study of the room-temperature synthesis of a SnO 2 /ZnO bilayer by magnetron sputtering. Morphological, optical, and electrical properties of the bilayer were investigated for different thicknesses of SnO 2 . Morphology was studied using profilometry and field emission scanning electron microscopy. The optical transmittances of the ZnO films and of the SnO 2 /ZnO combination were high (about 80%) in the visible, and the SnO 2 film did not alter the optical properties of the ZnO, which would… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…The maximum solar cell parameter values such as V oc , J sc , FF and η were recorded at 1.248533V, 31.35351045mA/cm 2 84.8548% and 33.2172%, respectively. These agreed with [35], experimentally, which revealed that, SnO 2 was deposited at a rate of around 2 nm/min, and its thickness ranged from ~30 to ~180 nm. Also, [36]showed that the thickness of the ETM signi cantly in uences solar cell optimization.…”
Section: Resultssupporting
confidence: 90%
“…The maximum solar cell parameter values such as V oc , J sc , FF and η were recorded at 1.248533V, 31.35351045mA/cm 2 84.8548% and 33.2172%, respectively. These agreed with [35], experimentally, which revealed that, SnO 2 was deposited at a rate of around 2 nm/min, and its thickness ranged from ~30 to ~180 nm. Also, [36]showed that the thickness of the ETM signi cantly in uences solar cell optimization.…”
Section: Resultssupporting
confidence: 90%
“…Therefore, a suitable doping selection mechanism is based on the high-impedance nature of the material. Based on this condition, PbO, Al 2 O 3 , and ZnO were utilized as a potential inorganic metal-oxide-doped SnO 2 ETL in PSCs, forming a double ETL [ 105 , 106 , 107 ]. Reference samples with bare FTO and FTO/SnO 2 are shown in the top-view SEM images in Figure 16 a–f [ 105 ].…”
Section: Doping Engineering Of Snomentioning
confidence: 99%
“…This preparation method is simple and effective, but the growth time of SnO 2 thin shells is up to 48 h, which is not suitable for mass production. ZnO possesses optical and electrical properties similar to those of SnO 2 , and it is known that the metal activity of Zn is more potent than that of Sn, which means that Zn is much more easily oxidized compared with Sn under the same conditions. Therefore, the growth of ZnO shells on the outer layer of the AgNWs is expected to take a shorter time than that of SnO 2 shells.…”
Section: Introductionmentioning
confidence: 99%